Ekspresi Gender pada Perempuan Karnivora dalam Shounen Manga - Nabila Vina Fairuzzahra (Universitas Diponegoro, 2025)
Carnivore women have become a phenomenon in Japan. Carnivore women is a term used to describe women whose characteristics are more aggressive and different from the traditional Japanese women’s behavior standard. This phenomenon has been represented in media, including manga. There are two mangas that seem to portray carnivore women through their plot, which are Takane no Hana Nara Ochitekoi!! and Boku no Kanojo wa Saikou Desu!. This research aims to analyze how the heroines in those mangas that are identified as carnivore women show their gender expression. This research uses Bem Sex-Role Inventory (BSRI) theory as well as qualitative descriptive approach with textual analysis method to carry out the analysis. The result of this research shows that both heroines from Takane no Hana Nara Ochitekoi!! and Boku no Kanojo wa Saikou Desu! show their gender expression mostly through masculine traits and behaviors, such as aggressive, masculine, dominant, and athletic. However, they also show it through feminine and androgyny traits and behaviors, although not as dominant as their masculine ones. It means that the portrayal of carnivore women represents a deconstruction of the gender expression of women while keeping some of the traditional feminity traits. <a href=